'We are having a very enjoyable game': Britain, sport and the South African War, 1899–1902. (January 2018) - Donaldson, Peter
This article explores the relationship between sport and war in Britain during the South African War, 1899–1902. Through extensive press coverage, as well as a spate of memoirs and novels, the British public was fed a regular diet of war stories and reportage in which athletic endeavour and organized games featured prominently. This contemporary literary material sheds light on the role sport was perceived to have played in the lives and work of the military personnel deployed in South Africa. It also, however, reveals a growing unease over an amateur-military tradition which equated sporting achievement with military prowess.